KONSEP DAKWAH DALAM PERSPEKTIF ABDURRAHMAN WAHID (GUS DUR) (STUDI ANALISIS METODE DAKWAH)
This study describes the da’wah concept of Abdurrahman Wahid in the study of da’wah analysis methods, which aims 1) to describe the concept of ’Abdurrahman Wahid’s da’wah, and 2) describe the Abdurrahman Wahid da’wah method. This research is a type of qualitative research through library research, using a normative approach, da’wah, and historical. The data collection method in this study was through collecting documents. The instrument in this study was the researcher himself (human instrument). The results of this study indicate, 1) Abdurrahman Wahid is a figure dai who has the character of pluralism with a moderate concept of da’wah. This is supported by the characteristics of preaching that upholds the principle of justice (al-‘adalah), the principle of balance (tawaz